2018
DOI: 10.1021/acscatal.8b01645
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal Synthesis of Ultrathin Monoclinic BiVO4 Nanosheets for Z-Scheme Overall Water Splitting under Visible Light

Abstract: Recently, ultrathin 2D photocatalysts have attracted people’s attention due to their performances in the area of solar energy conversion. However, the synthesis of ultrathin 2D photocatalysts with a nonlayered crystal structure is still full of challenges. Herein, ultrathin 2D BiVO4 nanosheets (NSs) with monoclinic crystal structure are synthesized through a convenient colloidal two-phase method. The as-prepared BiVO4 NSs possess a thickness of less than 3 nm but a diameter larger than 1.2 μm. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
117
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(118 citation statements)
references
References 54 publications
1
117
0
Order By: Relevance
“…Similar conclusions have also been drawn by other researchers. [19,34,37] Recently, various photocatalysts have been investigated for selective photocatalytic oxidation of benzyl alcohol to benzaldehyde, [38][39][40][41][42] and their activities are listed in Table S1. It is found that the 0.95Ru/3DOM BiVO 4 À Ar-300 sample showed better photocatalytic performance than most of the reported photocatalysts (except 0.3 wt % Pt/Bi 2 MoO 6 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar conclusions have also been drawn by other researchers. [19,34,37] Recently, various photocatalysts have been investigated for selective photocatalytic oxidation of benzyl alcohol to benzaldehyde, [38][39][40][41][42] and their activities are listed in Table S1. It is found that the 0.95Ru/3DOM BiVO 4 À Ar-300 sample showed better photocatalytic performance than most of the reported photocatalysts (except 0.3 wt % Pt/Bi 2 MoO 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Among the Bi-based semiconductors, BiVO 4 with an environmental benignity and a high stability has attracted much attention. [18][19][20] BiVO 4 is usually used in water splitting and environmental remediation, but only few studies on the photocatalytic synthesis of fine chemicals over BiVO 4 have been seen in the literature. [4,21] Furthermore, cheaper Ru in price than Pt could be used as a promising cocatalyst since it showed high selectivity in photocatalytic oxidation of toluene and good activity in photocatalytic reduction of CO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The morphology of nanomaterials has significant impacts on the interfacial energetics, kinetics and charge transport properties . Therefore, understanding and controlling the structural aspects of BiVO 4 photoanodes can provide an effective way to enhance its PEC performance .…”
Section: Strategies For Enhancing Pec Performancementioning
confidence: 99%
“…The morphology of nanomaterials has significant impacts on the interfacial energetics, kinetics and charge transport properties. [64][65][66][67] Therefore, understanding and controlling the structural aspects of BiVO 4 photoanodes can provide an effective way to enhance its PEC performance. [15,68] In this subsection, strategies developed to obtain desirable porosities and preferred crystal facets are reviewed.…”
Section: Morphological Controlmentioning
confidence: 99%
“…[5][6][7] Particularly, photogenerated charge separation is the key and bottleneck among three basic steps. To date, various adequate strategies have been explored for facilitating spatial charge separation of semiconductor-based photocatalysts like heterojunctions, [8][9][10][11][12] especially for heterophase junctions [13][14][15] have been recognized as an effective and common approach. The construction of the phase junction formed at the interface between two crystalline phases of a specific semiconductor is found to be useful in driving the spatial separation and transfer of the photogenerated electrons and holes under the function of the built-in electrical field, [16,17] which has been widely accepted to be validated in many semiconductor-based photocatalysts, such as typical TiO 2 , WO 3 , CdS, and ZnS.…”
Section: Introductionmentioning
confidence: 99%